Cathodoluminescence characterization of polystyrene–BaZrO3 hybrid composites - Savchyn, V.P.; Popov, A.I.; Aksimentyeva, O.I.; Klym, H.; Horbenko, Yu.Yu.; Serga, V.; Moskina, A.; Karbovnyk, I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
The radiation properties and the electronic structure of hybrid composites based on suspension polystyrene (PS) and nanocrystals of BaZrO3 (BZO) (d < 50 nm) have been studied using luminescent spectroscopy and x-ray analysis. A strong cathodoluminescence (CL) in BZO-nanocrystals is observed in temperature range 80–293 K. It is modified in BZO–PS composites: both the low- and a high-energy bands (near 4 eV) appear, to-gether with a significant reduction in the CL intensity. A decrease of the lattice parameter а for BZO phase in the composite and the modification of CL spectra indicate for changes in the nanocrystalline structure induced by the polymer.